DC Converter Experiment on Cu-Zn Seawater Battery for Fishing Lamp Energy Source of Lift Net Fisheries - Adi Susanto; Mulyono Baskoro; Sugeng Hari Wisudo; Mochammad Riyanto; Fis Purwangka (Jurnal Perikanan dan Kelautan, 2018)
Light fihing activities developed rapidly after the invention of electric lights. The innovation of Light Emitting Diode (LED) as energy saving lamp has a great opportunity to be used in fishing activities. LED lamps require low voltage and current, so that it can be combined with renewable energy sources to encourage more environmentally friendly of fishing capture activity. This study aims to determine the design and construction of an optimal DC converter using Cu-Zn seawater battery as an early stage of LED lamp development with seawater energy source for fixed lift net fishery. The research was conducted at Fishing Technology Laboratory, Department of Fisheries Resources Utilization, FPIK-IPB in August 2017. The treatments were number of windings (30:50, 50:80) and number of toroid (single, double) that was used in DC converter circuit. The energy source used comes from a single seawater battery cell with a zinc anode (Zn) and a copper cathode (Cu) with a size of 40x36 cm, inserted into a 3-inch diameter PVC tube. The voltage was measured by a digital oscilloscope (Iwatsu DS 5102), the current was measured using a multimeter (Sanwa CD 771) and the light intensity was measured using a lux meter. Differences in the number of windings and toroid have a significant effect on the value of inductance. Single Toroid with 80 loops produces the largest inductance value (143.1 mH) compared to other treatments. The use of DC converter with dual toroid and 50:80 winding provides better performance than other treatments with maximum voltage, current and intensity respectively 2.12 V; 121,80 mA and 128 lux